A study on the impact of China National Petroleum Corporation’s business strategies to Petronas in Sudan / Nurazuranie Osman - Osman, Nurazuranie (Faculty of Business and Management, 2010)
Asian national oil companies are prospering in Africa’s largest country but Western investment has been deterred by U.S. sanctions and political instability surrounding the referendum. CNPC, PETRONAS and ONGC are among the foreign oil firms in Sudan. CNPC and PETRONAS started its investment in Sudan in 1995. However, CNPC is the dominant foreign player in the Sudanese Oil Industry while PETRONAS is the second major player in Sudan. CNPC has used variety of business strategies in Sudan that have give impact to PETRONAS in Sudan. There are two types of impacts of CNPC’s business strategies to PETRONAS, which are positive impacts and negative impacts or threats. Thus, this study is intending to determine the business strategies used by CNPC in Sudan, the impact of CNPC’s business strategies to PETRONAS in Sudan and the gap analysis between the CNPC’s business strategies and PETRONAS business strategies in Sudan. Thus, from the findings of gap analysis, we can see that which business strategies that PETRONAS have been missed in Sudan compared to the CNPC.